Advanced Nanofiber-Based Scaffolds for Achilles Tendon Regenerative Engineering - Zhu, Senbo; He, Zeju; Ji, Lichen; Zhang, Wei; Tong, Yu; Luo, Junchao; Zhang, Yin; Li, Yong; Meng, Xiang; Bi, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: The Achilles tendon (AT) is responsible for running, jumping, and standing. AT injuries are very common in the population. The incidence of AT injuries in the adult population (21-60 years) is approximately 2.35 per 1000 persons. It seriously affects people's quality of life and increases the medical burden. AT has poor healing ability due to low cellularity and vascular deficiency. Therefore, AT injury healing has received great attention from researchers. Current AT injury treatment strategies cannot effectively restore the mechanical structure and function of AT, which promotes the development of tissue engineering methods. Tissue engineering simulations build tissue biosubstitutes and can replace (or help regenerate) diseased and injured tissue. Due to their structural similarity to natural tendons and their ability to promote regeneration, various advanced nanofiber scaffolds are currently being investigated. This review will briefly describes the anatomy and structure of AT. Focus on the importance of advanced nanofiber scaffolds in tissue engineering for AT injury repair, enhancement and regeneration.